2009
DOI: 10.1007/s00420-009-0398-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of occupational exposure to 1,4-dichlorobenzene on hematologic, kidney, and liver functions

Abstract: The higher urinary 2,5-DCP concentration in exposed (105.38 μg/L) than non-exposed (1.08 μg/L) workers suggests that 1,4-DCB exposure may increase the 2,5-DCP concentration in urine. Moreover, exposure to 1,4-DCB may also increase WBC count and ALT activity, and PPE may protect workers from 1,4-DCB exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…Pentachlorophenol, and its major metabolite tetrachlorohydroquinone, evoke hepatotoxicity in rats and human hepatoma cell lines (Wang et al, 2001). 1,4-dichlorobenzene exposure increases ALT activity and elevates the concentration of 2,5-DCP in urine (Hsiao et al, 2009). In our study, 2,4-DCP decreased cell viability and inhibited colony formation in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Pentachlorophenol, and its major metabolite tetrachlorohydroquinone, evoke hepatotoxicity in rats and human hepatoma cell lines (Wang et al, 2001). 1,4-dichlorobenzene exposure increases ALT activity and elevates the concentration of 2,5-DCP in urine (Hsiao et al, 2009). In our study, 2,4-DCP decreased cell viability and inhibited colony formation in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorinated phenols are toxic for a wide range of wildlife organisms and humans (Hsiao et al 2009; IPCS 1989; Takahashi et al 2011). In 1987, the International Agency for Research on Cancer (IARC) classified 1,4-D as a carcinogen in animals [IARC 1999; National Toxicology Program (NTP) 2011].…”
Section: Introductionmentioning
confidence: 99%
“…Although the best described adverse health effect of pDCB are carcinogenic in nature, other studies have reported that pDCB produces overt hematotoxicity, nephrotoxicity, hepatotoxicity, neurotoxicity, and damage to the lungs, both in experimental animals and humans [17,18,[52][53][54][55]. pDCB exposure has also been reported to induce addiction and resultant withdrawal encephalopathy [52].…”
Section: Discussionmentioning
confidence: 97%